ANALISIS MATERI KLASIFIKASI TUMBUHAN PADA BUKU TEKS PELAJARAN BIOLOGI SMA KELAS X KURIKULUM 2013 - Kun Ma’rifatin; Wan Syafi’i; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to know the level of suitability coverage of materials and components of material presentation Plant Classification in Biology textbook of Senior High School 10th Grade with Curriculum 2013 based on standard of BSNP. This research is a descriptive research with content analysis design. The content analysis in this study aims to describe the level of suitability coverage of materials Plant Classification from aspects coverage of material; consists of the breadth of material and the depth of material, and of the component of material presentation; consists of aspects techniques of material presentation, aspects supporting of material presentation, and aspects of learning presentation. Sampling of Biology textbook is conducted with purposive sampling technique, which should contain the concept of plant classification and written based on Curriculum 2013. The instruments used in this research were adopted from the BSNP assessment instruments in evaluating a textbook, by modifying and describing instrument descriptions according to the research objectives. The data collection technique in this study is documentary study. Plant Classification material contained in the Biology Textbook is then analyzed by researchers by analyzing each text, image, and table. The obtained data were analyzed descriptively quantitatively. The results showed the percentage suitability of the scope of the Plant Classification material in the book A was 93.59% and book B was 81.13%. While the presentation component of Plant Classification material in the book A is 92.5% and book B is 93.75%. Based on the results it can be concluded that the level of suitability of the scope of the Plant Classification material in the book A is very suitable and book B is suitable. The component of presentation of Plant Classification material in the book A and book B are very good.Key Words: Plant Classification, Coverage of Materials, Components of Material Presentation